Daily life difficulties among patients with ulcerative colitis in Japan and the United Kingdom: A comparative study. Issue 35 (2nd September 2022) - Kawakami, Aki; Tanaka, Makoto; Sakagami, Kayoko; Choong, Lee Meng; Kunisaki, Reiko; Maeda, Shin; Bjarnason, Ingvar; Ito, Hiroaki; Hayee, Bu'Hussain
Abstract : The difficulty of life scale (DLS) instrument is used to measure specific life problems in patients with ulcerative colitis (UC). Importantly, health care providers should consider the characteristics of the country in which they support patients with UC. This cross-cultural comparison study investigated DLS among patients with UC in Japan and the United Kingdom (UK). Outpatients attending one hospital in London and one in Osaka were included. We collected patient information using the DLS questionnaire, which comprises 18 items in three domains. Mean differences between Japan and the UK were compared for the total score and each domain of the DLS. Variables with P < .05 in univariate analysis were entered into a multiple regression model. We included 142 patients from Japan and 100 patients from the UK in the analysis. Univariate results showed that UK patients had more difficulties than Japanese patients in all three domains. Multivariate results showed that only "decline of vitality or vigor" showed significantly lower difficulty scores in Japanese patients. Having four or more bowel movements per day, visible bleeding, and being a homemaker or unemployed were significantly associated with greater difficulty according to the DLS total score. The level of daily life difficulties assessed using the DLS was greater among patients in the UK than among Japanese patients. This comparative study between patients with UC in Japan and the UK demonstrated certain country-related features for domain 3, "decline of vitality or vigor, " of the DLS. The reasons why UK patients felt greater decline in vitality or vigor may be that these patients may have symptoms other than bowel symptoms; also, Japanese patients are more hesitant to express discomfort. The findings of this study might lead to a better understanding of culturally sensitive perceptions of daily life difficulties in UC.